Pemberdayaan Remaja Sebagai Agen Perubahan Dalam Kampanye Kesehatan Reproduksi Di Desa Binaan - Riswanti Riswanti; Cakrawati Cakrawati; Andi Hariati; Baso Witman Adiaksa; Rizky Auliah Juniarti (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Adolescent reproductive health is a crucial issue in improving the quality of human resources in Indonesia. Lack of knowledge and awareness among adolescents regarding reproductive health can lead to risky behaviors, such as unintended pregnancies and sexually transmitted infections. This community service activity aimed to empower adolescents as change agents (peer educators) in reproductive health campaigns in Assisted Village X, Y District. The methods used included training, group discussions, educational simulations, and mentoring during community campaigns. Thirty adolescents aged 14–18 years participated in the program. Evaluation was conducted through pre-test and post-test questionnaires and direct observation. The results showed a 60% increase in knowledge, as well as improved communication skills and confidence in delivering health information. This activity demonstrates that adolescent empowerment is effective in developing their capacity as agents of change in the community while strengthening promotive and preventive efforts in reproductive health.